Target 10 – Productive Sectors - DeClerck, Fabrice A.J.; Navarrete Frías, Carolina; Jones, Sarah K.; Estrada-Carmona, Natalia; Barrios, Edmundo; Milano, Fernando; Obura, David; Leadley, Paul (2022)
The bioDISCOVERY programme of Future Earth and the Secretariat of the Group on Earth Observations Biodiversity Observation Network (GEO BON), convened a group of experts to prepare six briefs to provide scientific support for the negotiations of the post-2020 global biodiversity framework (GBF) at the fourth meeting of the Working Group on the Post-2020 Global Biodiversity Framework in Nairobi, from 21 to 26 June 2022. This includes four briefs on individual Targets 3, 7, 8 and 10, a brief on the GBF monitoring framework, and a brief on the ecosystem area and integrity objectives of the GBF that also addresses Targets 1 and 2 in detail. This science brief addresses the inclusion of sustainable agriculture of Target 10. The analysis in this brief focuses on the wording elements of Target 10, definitions of key terminology, evidence review of biodiversity in agriculture and assessment of the adequacy and availability of indicators for tracking the achievement of this target. This analysis is based on the text of the first draft of the post-2020 global biodiversity framework, CBD/WG2020/3/3 and subsequent negotiations of this text: Target 10. Ensure all areas under agriculture, aquaculture and forestry are managed sustainably, in particular through the conservation and sustainable use of biodiversity, increasing the productivity and resilience of these production systems This analysis focuses on sustainable agriculture emphasizing the current pressures that agriculture puts on nature which are currently a major source of degradation, and on the potential of sustainable practices to regenerate natures contributions to people, notably food, fuel, and fibre production, but also non production related contributions such as climate mitigation. It emphasizes that clear environmental performance metrics are necessary to monitor agriculture’s transition to net positive environmental values and highlights existing metrics validated by the scientific community.